Thin-film solid-state rechargeable lithium battery - Ribeiro, J. F. (2011)
This paper describes the optimization and the materials technology required for fabricating thin-film solid-state rechargeable lithium batteries. The following materials were selected, deposited and optimized: a glassy lithium-phosphorus oxynitride electrolyte (LiPON) between a lithium (Li) anode and crystalline lithium-cobalt dioxide cathode (LiCoO2), deposited by RF-sputtering. Ti/Pt layers, deposited by evaporation (using the e-beam technique) were used in contacts and a silicon nitride thin film (Si3N4), deposited by Hot-wire CVD protects the battery. This technology allows batteries with a potential of 4.5 V, typical capacities of 50 μA.cm-2 and charge discharge rates up to 4C.